Budaya Lokal dan Otonomi Daerah Dalam Kaitannya dengan Keistimewaan Yogyakarta - Jawahir Tantowi (Program Studi Ilmu Agama Islam Program Magister, Universitas Islam Indonesia, 2001)
The Act No. 22, 1999 on region autonomy has raised or appeared a problem for the special territory of Yogyakarta, especially in relation with the leader ship system regulation authority and possession of land. It happened when the principle of equality before the law and political rights of society were not accommodated well in the democratic concept reference. So, the harmonization between social realities of local society of Yogyakarta with the universal demand of democracy must be connected. Harmonization in this contexts means as an effort to explain some possibilities of how the effort takes a place when there is not adjustment between both demand of local value in reformation era and the democratic value. The wish to force one system without paying attention to another, cause the social dynamic will not grow well and the conducive society situation will not happen.